2017
DOI: 10.1016/j.heares.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The MMN as a viable and objective marker of auditory development in CI users

Abstract: In the present article, we review the studies on the use of the mismatch negativity (MMN) as a tool for an objective assessment of cochlear-implant (CI) functioning after its implantation and as a function of time of CI use. The MMN indexes discrimination of different sound stimuli with a precision matching with that of behavioral discrimination and can therefore be used as its objective index. Importantly, these measurements can be reliably carried out even in the absence of attention and behavioral responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 175 publications
2
30
0
12
Order By: Relevance
“…Some of our results are inconsistent with the previous data, and the discrepancy may be caused by different paradigm parameters of the experimental design (Chang et al, 2014 , 2017 ). Considering that the MMN index discrimination of various sound stimuli can result from a rigid matching similar to behavioral discrimination, the MMN signals are associated with the magnitude of deviation and involve perceptual discriminability (Näätänen et al, 2017 ). In SCD patients, auditory discrimination is different because we observed that the auditory frequency discrimination threshold ranges from 1,200 to 300 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Some of our results are inconsistent with the previous data, and the discrepancy may be caused by different paradigm parameters of the experimental design (Chang et al, 2014 , 2017 ). Considering that the MMN index discrimination of various sound stimuli can result from a rigid matching similar to behavioral discrimination, the MMN signals are associated with the magnitude of deviation and involve perceptual discriminability (Näätänen et al, 2017 ). In SCD patients, auditory discrimination is different because we observed that the auditory frequency discrimination threshold ranges from 1,200 to 300 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…A salient horizontal eye movement component was visually identified and removed in 9 of 11 CI users and 10 of the 14 NH. For each CI user, one to eight CI artifact components were visually identified and removed, based on whether their topographical centroids were located above the implant site (Viola et al, 2011;Näätänen et al, 2017) and their waveforms were distinguishable from ordinary auditory evoked responses and neurophysiological oscillations.…”
Section: Eeg Data Analysis and Statisticsmentioning
confidence: 99%
“…Statistical analysis on the MMN difference waves was conducted by following the clinical conventions of obtaining the average Fz electrode amplitude (Duncan et al, 2009;Näätänen et al, 2017) across a 30 ms time window centered on the feature-specific negative peak in the grand average ERP waveform (Näätänen et al, 2017). With the current stimulus paradigm and population samples, similar but slightly differing featurespecific MMN peak latencies were measured for each feature across groups: 148 ms for intensity, 156 ms for pitch, 132 ms for rhythm, and 152 ms for timbre MMN.…”
Section: Eeg Data Analysis and Statisticsmentioning
confidence: 99%
See 2 more Smart Citations